Concurrent Disorders Management in Psychiatric Care: Opportunities and Challenges. Issue 3 (September 2021) - Danilewitz, Marlon; Bahji, Anees; Lamba, Wiplove; Chopra, Nitin; George, Tony P.
Abstract : Despite increased awareness of the prevalence and burden of substance use disorders, there is limited access to addiction treatment services in Canada, including in psychiatric settings. While substance use disorders are highly comorbid and confer a poorer prognosis on psychiatric illnesses, psychiatric services are often ill-equipped in managing comorbid addictions. While there has slowly been an increase in recognition of this deficit in psychiatric training, there continues to be a deficit in concurrent disorder services in psychiatric care. A potential strategy to address this gap in clinical services is a concurrent disorder consult model. Herein, we outline a model for improved access to addiction treatment in psychiatric care and outline considerations for developing concurrent disorder consult services.